Management of a Laryngeal Venous Malformation With Nd:YAG Laser and Bleomycin Sclerotherapy. (11th November 2019) - Manna, Sayan; Meyer, Annika; Shigematsu, Tomoyoshi; Berenstein, Alejandro; Courey, Mark
Abstract : Literature describing neodymium:yttrium‐aluminum‐garnet (Nd:YAG) photocoagulation and sclerotherapy for laryngeal venous malformations (VMs) is sparse. Here we present a case in which an extensive laryngeal VM in a 28‐year‐old female was managed through a combination of four serial Nd:YAG laser photocoagulation sessions and four bleomycin injections over the course of 2 years. The treatment plan resulted in resulted in noticeable lesion ablation, mucosalization, and significant improvement in symptoms. To our knowledge, this case is the first instance of bleomycin injection specifically into a laryngeal VM reported in the English medical literature. Laryngoscope, 130:2199–2201, 2020